LOLEO AIRPORT REVIEW: CATALYST FOR SUSTAINABLE SHIFTING OF NORTH MALUKU’S CAPITAL TO SOFIFI - Rustam, Muhammad Syafril; Adisasmita, Sakti Adji; Aly, Sumarni Hamid; Abdurrahman , Muhammad Asad (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2026)
Fifteen years after it attained the administrative status of North Maluku's capital, Sofifi continues to suffer from political strife, infrastructural deficits and uneven spatial development, but Ternate is poised in terms of economic and social dominance. Filling the essential knowledge gap on whether airport-led infrastructure—airborne connectivity through the new Loleo Airport—can ignite Sofifi to function as an effective provincial capital, we investigate through the qualitative-descriptive approach regional planning reports (RTRW, RPJPD, RZWP3K), research and policy publications, spatial databases (land cover change, NDBI analysis), and on-site site visit in Sofifi and Ternate. Our research demonstrates airport-led development in connectivity can redirect cityward development inlandward, stimulate diversified economic activities—agritourism and logistics especially—and link marginalized sub-districts into larger transport systems. Furthermore, through integrating local wisdom in airport precinct planning and aligning legislative improvements with development planning, Loleo Airport is perceived as an integrating node reducing elite conflictiveness, leveling out deficiencies in service provision, and integrating cultural heritage. These findings underscore the necessity of marrying planned infrastructure expenditure with inclusive governance and spatial planning to attain balanced development and legitimate Sofifi as North Maluku's economic and administration capital. Abstrak Lima belas tahun setelah memperoleh status administratif sebagai ibu kota Maluku Utara, Sofifi terus menderita akibat perselisihan politik, defisit infrastruktur, dan pembangunan spasial yang tidak merata, sementara Ternate siap untuk mendominasi secara ekonomi dan sosial. Untuk mengisi kesenjangan pengetahuan penting tentang apakah infrastruktur berbasis bandara—konektivitas udara melalui Bandara Loleo yang baru—dapat mendorong Sofifi untuk berfungsi sebagai ibu kota provinsi yang efektif, kami melakukan investigasi melalui pendekatan kualitatif-deskriptif dengan menggunakan laporan perencanaan regional (RTRW, RPJPD, RZWP3K), publikasi penelitian dan kebijakan, basis data spasial (perubahan tutupan lahan, analisis NDBI), dan kunjungan lapangan di Sofifi dan Ternate. Penelitian kami menunjukkan bahwa pembangunan berbasis bandara dalam hal konektivitas dapat mengarahkan pembangunan kota ke pedalaman, merangsang kegiatan ekonomi yang beragam—terutama agrowisata dan logistik—dan menghubungkan kecamatan-kecamatan yang terpinggirkan ke dalam sistem transportasi yang lebih besar. Lebih lanjut, melalui pengintegrasian kearifan lokal dalam perencanaan kawasan bandara dan penyelarasan perbaikan legislatif dengan perencanaan pembangunan, Bandara Loleo dipandang sebagai pusat integrasi yang mengurangi konflik antar elit, meratakan kekurangan dalam penyediaan layanan, dan mengintegrasikan warisan budaya. Temuan ini menggarisbawahi perlunya menggabungkan pengeluaran infrastruktur yang direncanakan dengan tata kelola inklusif dan perencanaan spasial untuk mencapai pembangunan yang seimbang dan melegitimasi Sofifi sebagai ibu kota ekonomi dan administrasi Maluku Utara.